2000
DOI: 10.1038/sj.cgt.7700261
|View full text |Cite
|
Sign up to set email alerts
|

An improved intravesical model using human bladder cancer cell lines to optimize gene and other therapies

Abstract: Orthotopic implantation of human bladder cancer cells into immunodeficient mice is an important tool for studying the biology and effects of therapy. Nevertheless, the incidence of tumor implantation and growth by transurethral instillation of the human bladder cancer cells into murine bladders has been low or not reproducible. However, using a modified intravesical technique and the human bladder cancer cell lines, KU -7 and UM -UC -2, we have been able to obtain a high and reproducible incidence of superfici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 10 publications
0
52
0
Order By: Relevance
“…7 Ad-IFNa2a1 12 and AdIFNa2b 13 are both E1-deleted adenoviral constructs with the E1 region replaced with a CMV promoter driving the IFN transgene including the secretory leader sequence. Ad-IFNa2a1 is identical to Ad-IFNa2b except that the Ad-IFNa2a1 transgene is comprised of the cDNA that encodes the N-terminus of the human IFNa2b fused to the C-terminus of the human IFNa1 through a BglII restriction site ((Hu-IFN-aA/D (BglII)), whereas the AdIFNa2b contains the transgene for the human IFNa2b gene.…”
Section: Cell Lines Vectors and Syn3mentioning
confidence: 99%
See 2 more Smart Citations
“…7 Ad-IFNa2a1 12 and AdIFNa2b 13 are both E1-deleted adenoviral constructs with the E1 region replaced with a CMV promoter driving the IFN transgene including the secretory leader sequence. Ad-IFNa2a1 is identical to Ad-IFNa2b except that the Ad-IFNa2a1 transgene is comprised of the cDNA that encodes the N-terminus of the human IFNa2b fused to the C-terminus of the human IFNa1 through a BglII restriction site ((Hu-IFN-aA/D (BglII)), whereas the AdIFNa2b contains the transgene for the human IFNa2b gene.…”
Section: Cell Lines Vectors and Syn3mentioning
confidence: 99%
“…The methods for growing superficial KU7/GFP human bladder tumors in athymic mice and their imaging have previously been described. 7,8 At 2 weeks after the tumor cells were intravesically instilled, the bladders were imaged for the presence of GFP-containing tumors. Anterior, posterior, as well as left lateral and right lateral views were taken as previously described.…”
Section: Superficial Tumor Formation Treatment and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The cells were maintained in Earl's MEM containing 10% fetal bovine serum and 50 U / mL of penicillin and streptomycin.…”
Section: Human Bladder Cancer Cell Linementioning
confidence: 99%
“…2 In addition, our laboratory in collaboration with others has shown that this model can be used to document efficient intravesical adenoviral -mediated gene transfer when it is combined with the polyamide compound, Syn 3. 3 Our next challenge was to use this tumor model in vivo to examine the efficacy of various treatments and schedules.…”
mentioning
confidence: 99%